Statins and its hepatic effects: Newer data, implications, and changing recommendations - Jimmy Jose (Wolters Kluwer Medknow Publications, 2016)
Hepatic adverse effects are one of the most commonly known adverse effects reported with statins. Frequently, fear of serious hepatic effects contributes to underutilization of statins as well as unnecessary discontinuation of its use among those indicated. There are changing data on the occurrence of these negative hepatic effects, recommendations on their actual risk, monitoring required, and safety of use in those with preexisting hepatic disorders. Based on reviewed literature, statins appear to be associated with a very low risk of true and serious liver injury. Unprecedented fears regarding hepatic adverse effects of statins among prescribers and patients can deny patients of the significant benefits of these agents. Routine periodic monitoring of liver function does not appear to detect or prevent serious liver injury and hence may not be indicated. But the potential of statins to cause significant and serious hepatic effects should not be overlooked in daily clinical practice. Statin use need not be avoided in patients with preexisting liver dysfunction such as nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, compensated cirrhosis, and compensated chronic liver disease if its use is clearly indicated. Physician's judgment based on the risk and benefit for an individual patient does matter when a strategy is chosen regarding the use of statins and monitoring patients while on statins.